Evaluation of the epidemiology of pneumothorax in Bhuj district: a population based survey - Chaudhary, Anand; Pujara, Nishant (International Journal of Advances in Medicine, 2017)
Background: Pneumothorax is an abnormal collection of air in the pleural space that causes an uncoupling of the lung from the chest wall. It may be spontaneous or traumatic. The spontaneous pneumothorax is usually the result of rupture of superficial emphysematous bullae and may occur in apparently healthy persons or in association with chronic pulmonary disease. It is usually unilateral but may be bilateral. If air reaches the mediastinum and rupture into both the pleural cavity. Methods: 25 consecutive cases of pneumothorax admitted at the Gujarat Adani institute of medical science Bhuj from December 2011 to April 2012 were studied. Each patient was interrogated and examined in detail according to the attached proforma, with a view to identify the nature of pneumothorax. Results: The incidence of pneumothorax was maximum in the 4th decade of life. The youngest one was a boy ages 14 year, while the oldest case was 75 years. 36 cases were under the age of 50 years, while only 2 cases were more than 70 years of age. Conclusions: The prevalence of pneumothorax was greater in male as compared to female. Most of the cases treated with needle aspiration of air and the intercostal drainage through indwelling polyethylene catheter developed surgical emphysema on the affected side which disappeared within 2-3 days after aspiration if air with needle or after removal of polyethylene tube from intercostal space.